UPAYA MENINGKATKAN PEMAHAMAN KARIR : IMPLEMENTASI ROLE PLAY GAME MELALUI SIMULASI PROFESI DI SD NEGERI 1 DENBANTAS KECAMATAN TABANAN - Juliawan Wayan; Ni Wayan Suastini; Satria Ardie Wibawa; Gita Pradnyani; Cahya Paramitha (Sewagati, 2025)
This community service activity aims to improve students’ career understanding through the Role-Playing Games (RPG) method, focusing on sixth-grade students at SDN 1 Denbantas. This method was implemented through stages of instruction, mentoring, observation, and evaluation (pre-test and post-test). The results show an increase in post-test scores in students’ career understanding, with an average score improvement of 0.64 after the implementation of the role-play game. In addition, this method also succeeded in enhancing students’ social skills, such as communication and collaboration. Its impact includes increasing students’ enthusiasm for learning and motivating them to explore career options. Furthermore, this activity provides positive benefits for the partner school as a reference in developing more interactive and effective career learning approaches